2016
DOI: 10.1021/acs.inorgchem.6b01858
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Chemical Reactivity between Carbon Dioxide and Three Transition Metals (Au, Pt, and Re) at High-Pressure, High-Temperature Conditions

Abstract: The role of carbon dioxide, CO, as oxidizing agent at high pressures and temperatures is evaluated by studying its chemical reactivity with three transition metals: Au, Pt, and Re. We report systematic X-ray diffraction measurements up to 48 GPa and 2400 K using synchrotron radiation and laser-heating diamond-anvil cells. No evidence of reaction was found in Au and Pt samples in this pressure-temperature range. In the Re + CO system, however, a strongly-driven redox reaction occurs at P > 8 GPa and T > 1500 K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
2
23
1
Order By: Relevance
“…It is important to stress that the experimental results reported here do not explain the Raman spectrum reported by Santoro et al 5 for the Si 0.4 C 0.6 O 2 solid solution after temperature quenching. β-ReO 2 Raman scattering is largely different8. The present results, however, raise substantial doubts on the phase assignment of the high-pressure high-temperature silicon carbon oxide phase.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…It is important to stress that the experimental results reported here do not explain the Raman spectrum reported by Santoro et al 5 for the Si 0.4 C 0.6 O 2 solid solution after temperature quenching. β-ReO 2 Raman scattering is largely different8. The present results, however, raise substantial doubts on the phase assignment of the high-pressure high-temperature silicon carbon oxide phase.…”
contrasting
confidence: 67%
“…When Re was used as a heater, a new phase was synthesized at pressures of 8 and 24 GPa and temperatures of 1,500–1,600 K. A more in-depth manuscript on the reactivity of transition metals and CO 2 has been recently published8. This new phase coexists with stishovite, and it is present up to 48 GPa and also during the entire decompression process down to ambient conditions.…”
mentioning
confidence: 99%
“…The long-standing quest of novel compounds within the CO2:SiO2 system has recently taken a step forward after considering simultaneous high-pressure (HP) and high-temperature (HT) conditions [1][2][3][4][5]. In particular, a recent study reported the synthesis of a silicon carbonate phase by reacting a well-known SiO2 zeolite, silicalite, with the molecular CO2 that fills the pores at [18][19][20][21][22][23][24][25][26] GPa and 600-980 K [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical total-energy studies have predicted novel silicon carbonate phases at HP-HT and their results need to be experimentally confirmed [8][9][10]. Note that the supposedly advantage of using zeolites to maximize surface chemical reactivity due to the large effective interaction area between the framework SiO2 and the confined-CO2 seems to be restricted to temperatures below 1300 K [3,4]. Above that temperature, zeolites transform into the thermodynamically stable phase of SiO2 at the corresponding pressure, from quartz to stishovite.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to record full 2-dimensional temperature maps in real time allows quantification of the thermal gradients and thermal pressure effects encountered during such experiments. The potential for creating new material with interesting physical properties using combined high pressure and high temperatures as achieved in a LHDAC has been demonstrated by a series of 12.2.2 experiments, which created, among others, novel transition metal nitrides, borides, and carbides (e.g., Kaner et al [24], Chung et al [25], Mohammadi et al [26], Friedrich et al [27,28], and Santamaria-Perez et al [29]). Equally interesting is the possibility of exploring P-T phase diagrams and thermo-elastic properties of (Earth-) materials at very high pressures and temperatures (e.g., Armentrout and Kavner [30], Nisr et al [31]).…”
Section: In-situ Laser Heatingmentioning
confidence: 99%